2013
DOI: 10.1007/s00441-013-1734-3
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted tight junctions in the small intestine of cystic fibrosis mice

Abstract: The tight junction (TJ) is the major determinant of paracellular permeability, which in the gut protects the body from entry of harmful substances such as microbial components. In cystic fibrosis (CF) there is increased permeability of the small intestine both in humans and in CF mice. To gain insight into the mechanisms of increased intestinal permeability in CF, I analyzed the composition of the TJ in the cystic fibrosis transmembrane conductance regulator (Cftr) knockout mouse model. Significant changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 69 publications
5
33
0
Order By: Relevance
“…Foremost is the inflammatory landscape in the GI tract observed in CF patients, a phenotype that is modeled well in Cftr intestinal-specific knockout mice. In both human CF patients and Cftr knockout mice there is impaired mucosal barrier function, including disrupted tight junctions, 28 that leads to compromised resistance to bacterial colonization, 29 infection, and abnormal innate and adaptive immune responses and inflammation, factors that together may promote oncogenesis. 1,21,30,31 Increased epithelial permeability is also a major factor in bicarbonate loss in the inflamed colon.…”
Section: Discussionmentioning
confidence: 99%
“…Foremost is the inflammatory landscape in the GI tract observed in CF patients, a phenotype that is modeled well in Cftr intestinal-specific knockout mice. In both human CF patients and Cftr knockout mice there is impaired mucosal barrier function, including disrupted tight junctions, 28 that leads to compromised resistance to bacterial colonization, 29 infection, and abnormal innate and adaptive immune responses and inflammation, factors that together may promote oncogenesis. 1,21,30,31 Increased epithelial permeability is also a major factor in bicarbonate loss in the inflamed colon.…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about how these cell–cell adhesion molecules are regulated during wound repair. Interestingly, CFTR has been previously shown to be interacting with junctional complexes (Castellani et al, ; Sun et al, ; De Lisle, ) and recently demonstrated to be involved in epithelial‐mesenchymal‐transition (EMT) and cancer metastasis in breast and colon cancer cells (Zhang et al, ; Sun et al, ). These results are consistent with the presently demonstrated important role of CFTR in the regulation of adhesion molecules, such as ZO‐1 and β‐catenin (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Acting as a hub, CFTR also stabilizes the apical junction complex through actin‐dependent interactions in epithelial cells so that the loss of apical protein networks orchestrated by CFTR has emerged as a common mechanism of increased permeability in CF epithelia, including gut and bile ducts . A disruption of tight junctions that could explain increased permeability has thus been demonstrated in the small intestine of CF mice …”
Section: Discussionmentioning
confidence: 99%